Effect of Nb and Si Content on Phase Stability, Microstructure and Mechanical Properties of Sintered Ti–Nb–Si Alloys - Derek Manoel Luup Carvalho; Deivison Daros Paim; Isadora Schramm Deschamps; Claudio Aguilar; Aloísio Nelmo Klein; Francisco Cavilha Neto; Guilherme Oliveira Neves; Cristiano Binder (Metals)
The development of beta titanium alloys with biocompatible elements to replace Al and V is a subject of significant interest in the biomedical industry. This approach aims to enhance biocompatibility and mitigate potential cytotoxic effects associated with traditional alloying elements. In this work, Ti–xNb–ySi alloys were produced using powder metallurgy, with x of 35, 40, and 45 wt.%, and y of 0.10, 0.35, and 0.60% wt.%, using a <semantics>32</semantics> experimental design. Milling was used to mix and disperse the powders, followed by cold pressing, sintering, and heat treatment. Nb was the main element used to stabilize the β phase, and Si was used to form Si precipitates, although Si also exhibits a β-stabilizing effect. It was found that an increase from 0.10 to 0.35 wt.% of Si improved relative density, with no benefits observed at 0.60 wt.% Si. Electron microscopy showed the presence of β phase grains, and grains with β + α intragranular structures and precipitates. Increasing Nb content resulted in a decrease in ultimate tensile strength while increasing Si content from 0.10% to 0.35 wt.% exhibited the opposite effect.